BCT563: Modular coordination & standardisations / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2020)
Student enrolled for this course will learn in general the construction terminology, materials, machinery & equipment and installing sequences of construction process. Student will be given a project and they will be required to propose a suitable method of constructions and prepare the construction methods for that particular project by using the latest technology available in construction industry. It will cover areas of open/close system and tolerances in Malaysia Standard etc.